1989
DOI: 10.1136/jnnp.52.8.980
|View full text |Cite
|
Sign up to set email alerts
|

EEG spectral analysis in delirium.

Abstract: SUMMARY Spectral analysis of EEG was conducted for 51 elderly delirious patients meeting the Diagnostic and Statistical Manual of Mental Disorders III (DSM-III) criteria and for 19 controls. As a whole group, and also when subdivided according to the type of delirium, severity of cognitive decline or the type ofcentral nervous system disease, delirious patients showed significant reductions of alpha percentage, increased theta and delta activity and slowing of the peak and mean frequencies and these changes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 37 publications
5
70
1
1
Order By: Relevance
“…In contrast, all cognitive and thought process abnormalities, and key diagnostic features were comparable across clinical subtypes. Therefore, our study using detailed assessment of a range of cognitive domains on the DRS-R98 and CTD, concurs with previous cross-sectional studies in elderly medical and consultation-liaison populations that found comparable cognitive and EEG abnormalities across motor subtypes of delirium [15,[35][36][37]. Overall, phenomenological studies suggest that cognitive and contextual items (i.e.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, all cognitive and thought process abnormalities, and key diagnostic features were comparable across clinical subtypes. Therefore, our study using detailed assessment of a range of cognitive domains on the DRS-R98 and CTD, concurs with previous cross-sectional studies in elderly medical and consultation-liaison populations that found comparable cognitive and EEG abnormalities across motor subtypes of delirium [15,[35][36][37]. Overall, phenomenological studies suggest that cognitive and contextual items (i.e.…”
Section: Discussionsupporting
confidence: 84%
“…These EEG results confirm previous findings reported in standard and spectral EEG in delirious patients [20][21][22][23]. However, EEG analysis is a relatively extensive and time-consuming method for use in daily clinical practice, and it would therefore be helpful to have another objective parameter for detecting delirium when the clinical diagnosis is unclear.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, patients receiving long-term medication for psychiatric and neurological disorders not included. Furthermore, to compare EEGs of ICU patients under the same sedative conditions, centrally acting anticholinergic drugs such as neuroleptics, benzodiazepines, and barbiturates, which are often administered during anaesthesia and on the ICU [21,33,34] and which have been associated with high SAA levels and delirium [35], were excluded from the present analysis (with the exception of piritramide). In addition, other endogenous sources of SAA have been postulated [13,24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in agreement with previous studies [14], a lower RASS was associated with a lower BIS index in this study. The lower BIS EEG in delirious patients obtained in our present study confirm previous findings using standard and spectral EEG [11,26,27], our previous results using a 16-channel EEG [12], and also in part the results of Ely et al [14] using a monolateral BIS EEG technique.…”
Section: Bis Eegsupporting
confidence: 82%